2008
DOI: 10.1017/s0033291708003401
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of psychic and somatic symptoms in adult patients with generalized anxiety disorder: examination from a duloxetine, venlafaxine extended-release and placebo-controlled trial

Abstract: Duloxetine and venlafaxine treatment were each efficacious for improvement of core psychic anxiety symptoms and associated somatic symptoms for adults with GAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 22 publications
3
55
0
2
Order By: Relevance
“…The efficacy of duloxetine for the treatment of GAD has been demonstrated in five large, double-blind, randomized trials (Davidson et al, 2008;Hartford et al, 2007;Koponen et al, 2007;Nicolini et al, 2008;Rynn et al, 2008). Further, this agent has demonstrated efficacy in animal models of persistent pain and in clinical studies of pain associated with diabetic neuropathy Raskin et al, 2005;Wernicke et al, 2006), fibromyalgia (Arnold et al, 2004(Arnold et al, , 2005Russell, Mease et al, 2008), and depression (Goldstein et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of duloxetine for the treatment of GAD has been demonstrated in five large, double-blind, randomized trials (Davidson et al, 2008;Hartford et al, 2007;Koponen et al, 2007;Nicolini et al, 2008;Rynn et al, 2008). Further, this agent has demonstrated efficacy in animal models of persistent pain and in clinical studies of pain associated with diabetic neuropathy Raskin et al, 2005;Wernicke et al, 2006), fibromyalgia (Arnold et al, 2004(Arnold et al, , 2005Russell, Mease et al, 2008), and depression (Goldstein et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, duloxetine has been shown to reduce painful physical symptoms associated with depression (Goldstein et al, 2004). In more recent clinical studies, duloxetine was also found to effectively reduce somatic symptoms and pain severity in patients with GAD Nicolini et al, 2008;Russell, Weisberg et al, 2008). Because previous analyses were based on the subgroup of patients who had clinically significant pain levels (visual analogue scale [VAS] scores !30 at baseline) Russell, Weisberg et al, 2008), additional investigation of the effect of duloxetine on painful physical symptoms in GAD patients from the overall clinical trial population would be informative to describe the presence and course of painful physical symptoms in patients with GAD.…”
mentioning
confidence: 99%
“…In comparator studies, it was more effective than placebo and as effective as pregabalin (Montgomery et al 2006b) and duloxetine (Hartford et al 2007;Nicolini et al 2008). In a further comparator study, it was more effective than buspirone (Davidson et al 1999); however, scores were only significantly lower for HAM-A psychic anxiety factor, anxious mood, and tension, but not for HAM-A total and CGI for venlafaxinetreated patients than for placebo-treated patients.…”
Section: Generalized Anxiety Disorder (Gad)mentioning
confidence: 95%
“…Á Duloxetine was more effective than placebo in DBPC studies (Koponen et al 2007;Rynn et al 2007aRynn et al , 2008. Also, in three-arm studies, both duloxetine and the comparator venlafaxine were better than placebo (Hartford et al 2007;Nicolini et al 2008). Two studies with a placebo and a venlafaxine arm were pooled in order to ensure adequate statistical power for a non-inferiority trial.…”
Section: Generalized Anxiety Disorder (Gad)mentioning
confidence: 99%
“…A further comparative study of duloxetine and venlafaxine was performed in 33 non-US sites (Nicolini et al 2008). Diagnostic criteria were substantially the same as those used in the previous trials with the HAM-A scale as the primary efficacy measure.…”
Section: Use Of Duloxetine In Generalized Anxiety Disordermentioning
confidence: 99%